2006
DOI: 10.1007/s00542-006-0272-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality factor of micro cantilevers transduced by piezoelectric lead zirconate titanate film

Abstract: The quality factors (Q-factor) of micro cantilevers transduced by piezoelectric lead zirconate titanate (PZT) film under atmospheric pressure conditions were investigated and discussed. It was found that Q-factors increased with thicker PZT film. Due to air damping, shorter cantilevers resulted in preferred larger Q-factors. The Q-factor was found to be as high as 450 for a 150-lm long PZT cantilever when using 1.04-lm thick PZT film as the electromechanical conversion medium. Differences in the measured Q-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Novel sensing methods for PAS have been proposed, such as quartz-enhanced photoacoustic spectroscopy (QEPAS) 8588 and cantilever-enhanced photoacoustic spectroscopy (CEPAS). 8994 For an in-depth review of PAS techniques, the reader is referred to other publications. 9597 A comprehensive review of the recent development and progress of infrared PAS techniques to 2011 was reported by Li et al 98…”
Section: Modern Laser Spectroscopy Techniquesmentioning
confidence: 99%
“…Novel sensing methods for PAS have been proposed, such as quartz-enhanced photoacoustic spectroscopy (QEPAS) 8588 and cantilever-enhanced photoacoustic spectroscopy (CEPAS). 8994 For an in-depth review of PAS techniques, the reader is referred to other publications. 9597 A comprehensive review of the recent development and progress of infrared PAS techniques to 2011 was reported by Li et al 98…”
Section: Modern Laser Spectroscopy Techniquesmentioning
confidence: 99%
“…However, our recent efforts reveal that the energy dissipation from intrinsic loss of the PZT thin film was comparable to air dumping under atmospheric pressure. Under reduced pressures, the energy dissipation from the PZT thin film became predominant (Lu et al 2006a(Lu et al , 2007a. Those extraordinary large energy dissipation greatly degraded sensitivity of the microcantilever, since quality factor (Q-factor) of a cantilever is inversely proportional to the rate of energy dissipation, and it determines the minimum detectable frequency shift Df after loading-mass Dm adsorption as indicated by Eq.…”
Section: Introductionmentioning
confidence: 99%
“…For chemical and biological sensing, the surface of microresonators can be covered with a sensitive coating to absorb the chemical and biological species [ 21 , 22 ]. Several microresonators also use piezoelectric multilayers due to their advantages such as compact structure, low driving voltage, self-actuation and self-sensing capability, and easy integration with electronic circuits [ 23 ].…”
Section: Introductionmentioning
confidence: 99%